Purine synthesis suppression reduces the development and progression of pulmonary hypertension in rodent models. (31st January 2023) - Ma, Qian; Yang, Qiuhua; Xu, Jiean; Sellers, Hunter G; Brown, Zach L; Liu, Zhiping; Bordan, Zsuzsanna; Shi, Xiaofan; Zhao, Dingwei; Cai, Yongfeng; Pareek, Vidhi; Zhang, Chunxiang; et al.
Abstract: Aims: Proliferation of vascular smooth muscle cells (VSMCs) is a hallmark of pulmonary hypertension (PH). Proliferative cells utilize purine bases from the de novo purine synthesis (DNPS) pathways for nucleotide synthesis; however, it is unclear whether DNPS plays a critical role in VSMC proliferation during development of PH. The last two steps of DNPS are catalysed by the enzyme 5-aminoimidazole-4-carboxamide ribonucleotide formyltransferase/inosine monophosphate cyclohydrolase (ATIC). This study investigated whether ATIC-driven DNPS affects the proliferation of pulmonary artery smooth muscle cells (PASMCs) and the development of PH. Methods and results: Metabolites of DNPS in proliferative PASMCs were measured by liquid chromatography-tandem mass spectrometry. ATIC expression was assessed in platelet-derived growth factor-treated PASMCs and in the lungs of PH rodents and patients with pulmonary arterial hypertension. Mice with global and VSMC-specific knockout of Atic were utilized to investigate the role of ATIC in both hypoxia- and lung interleukin-6/hypoxia-induced murine PH. ATIC-mediated DNPS at the mRNA, protein, and enzymatic activity levels were increased in platelet-derived growth factor-treated PASMCs or PASMCs from PH rodents and patients with pulmonary arterial hypertension. In cultured PASMCs, ATIC knockdown decreased DNPS and nucleic acid DNA/RNA synthesis, and reduced cell proliferation. Global or VSMC-specific knockout of Atic attenuated vascular remodelling and inhibited the development and progression of both hypoxia- and lung IL-6/hypoxia-induced PH in mice. Conclusion: Targeting ATIC-mediated DNPS compromises the availability of purine nucleotides for incorporation into DNA/RNA, reducing PASMC proliferation and pulmonary vascular remodelling and ameliorating the development and progression of PH. Structured Graphical Abstract: Structured Graphical Abstract Left panel: For vascular smooth muscle cells (VSMCs) of normal pulmonary artery, low levels of growth signals result in a low level of de novo purine synthesis and RNA and DNA production, maintaining haemostasis of VSMCs. Right panel: For VSMCs of pulmonary artery of pulmonary hypertension (PH), high levels of growth signals give rise to increased expression of purine-associated genes including ATIC, enhanced de novo purine synthesis and RNA and DNA production, promoting VSMC proliferation, and thickness of the pulmonary arterial wall. AMP, adenosine monophosphate; ATIC, 5-aminoimidazole-4-carboxamide ribonucleotide formyltransferase/inosine monophosphate cyclohydrolase; GMP, guanosine monophosphate; IMP, inosine monophosphate.